HUMANITARIAN FACTS IN THE NOVEL 'EL' BY LULUK HF BASED ON THE PERSPECTIVE OF LUCIEN GOLDMAN - Hidayah, Rosa; Mudhakir, Siti Latifah Nanda; Faisol, M.; Latifah, Nur (Annual International Conferences on Language, Literature, and Media, 2023)
This paper analyzes humanitarian aspects in the literary work titled "EL" by Luluk HF. This study aims to describe humanitarian facts related to individual and social facts based on the genetic structuralism theory proposed by Lucien Goldmann. A qualitative method is used in this research to explore the humanitarian facts present in the novel "EL." The conclusion is that the novel "EL" contains three types of humanitarian facts: individual humanitarian facts, humanitarian facts related to society, and social humanitarian facts related to the economy. Further research will utilize the genetic structuralism method more extensively, as it provides a more comprehensive approach to viewing and analyzing literary works from various perspectives.